Interaction of electrical conductivity and humic acids on yield and nutraceutical quality of Capsicum annuum L. fruits cv Arista (Bioagro, 2024)
The humic substances are an alternative to reduce excessive doses of fertilizers in cultivated species. The objective was to evaluate the effect of levels of electrical conductivity (EC) of the nutrient solution and doses of humic acids (HA) on the yield and quality of chili fruits (Capsicum annuum L.). The design was completely randomized with a bifactorial arrangement with 12 treatments and 15 replications. The factor one was the levels of EC of nutrient solutions (1.0, 1.5 and 2.0 dS·m-1); the factor two was the doses of HA (0, 2.5, 3.75, and 5.0 mL·L-1). The yield, length, equatorial diameter, epicarp thickness, firmness, weight, and number of fruits were evaluated. The nutraceutical quality was also evaluated (total phenols, capsaicin, antioxidant capacity and total flavonoids). The results showed that the yield, length, equatorial diameter, weight, and number of fruits showed differences between EC, while, yield, length, thickness of the pericarp, weight and number of fruits showed differences for HA. The fruit firmness showed differences in the interaction EC×HA. Most of the variables showed higher values in 1.0 dS·m-1 of EC and 2.5 of HA; the firmness was higher in 2.0 dS·m-1 of EC and 3.75 mL·L-1 of HA. The content of phenols, flavonoids, antioxidants, and capsaicin showed differences between EC, while flavonoids did not show differences for HA. The four variables showed differences in the interaction of the factors, with increases of 1.0 and 1.5 dS·m-1 of EC and 5.0 mL·L-1 of HA. The HA are an alternative to increase the yield of chili fruits and their nutraceutical quality.
Keywords: Antioxidant capacity; capsaicin; flavonoids; phenols; yield components